Effect of cooling medium temperature on cooling curve and microstructure of Ti65 alloy - DONG Xiaolin; LI Wenyuan; TAN Haibing; LIU Jianrong; LIU Qiaomu; CHEN Yulong; WANG Lei; WANG Qingjiang (Cailiao gongcheng)
The cooling rate after high-temperature heat treatment has a significant effect on the microstructure and properties of Ti65 alloy. The effect of cooling medium temperature on the cooling curve and microstructure of Ti65 alloy after high-temperature heat treatment has been systematically studied. The results show that the temperature of the oil medium has an opposite effect on the cooling curve to that of the air medium. The maximum cooling rate of oil is 73.2 ℃/s at room temperature， while the maximum cooling rate of air cooling is only 11.2 ℃/s. As the temperature increases， the cooling rate curve for oil quenching condition shifts to the right， and the maximum cooling rate and the minimum film boiling temperature increase. When the oil temperature is in the range of room temperature to 60 ℃， the cooling rate curve for oil quenching condition includes vapor， boiling， and convection three stages. When the oil temperature rises to 80 ℃， the vapor stage disappears. In addition， the microstructure shows a transition trend from α+β dual-phase microstructure to martensitic microstructure with the increase in oil temperature. Conversely， with the temperature increases， the cooling rate curve for air cooling condition shifts to the left， the maximum cooling rate decreases， and the temperature at the maximum cooling rate in the boiling stage gradually increases. Compared with oil quenching at different temperatures， the microstructure of air cooling under different temperatures shows typical bimodal microstructure with no obvious difference. The effect of oil temperature on the cooling curve is mainly attributed to changes in oil viscosity and fluidity， while the effect of air temperature on the cooling curve is mainly attributed to multiple complex factors such as air density and temperature gradient.